The role of organoclay on the properties of Polymethylsilsesquioxane: A systematic study. Issue 12 (2nd December 2017) - Alex, Ancy Smitha; Rajeev, R.S.; Sekkar, V.; Gouri, C.
ABSTRACT: In this study, an attempt is made to improve the properties of PMSQ, an organosilicone polymer which possesses distinguished properties, through an easy and facile route by the inclusion of organically modified montmorillonite clay. PMSQ-clay composites were prepared by solution blending of the components initially and then heat curing under load. The effect of clay content, varied at 5–40 wt.%, on mechanical, thermal and dynamic mechanical properties was evaluated and the optimum was obtained for 20%. Morphology investigation as well as microstructure analysis revealed intercalated to exfoliated morphology of PMSQ-clay composite. An appreciable improvement in mechanical properties of PMSQ, compressive strength and impact strength in particular, was achieved by clay inclusion up to 20%. The properties declined at ≥ 30% clay loading. The composites showed increased thermal stability compared to unmodified PMSQ up to 400 °C. Also, increase in clay content accelerated conversion to ceramic SiOC. PMSQ-clay composites exhibited good visco-elastic characteristics with higher Tg probably due to enhanced polymer-clay interactions. Thus, a simple and viable method to enhance the mechanical and thermal characteristics of PMSQ by way of preparing its composite with the reinforcing filler organoclay is demonstrated here.